The identification of genes from the oyster Crassostrea gigas that are differentially expressed between progeny exhibiting opposed susceptibility to summer mortality - Huvet, Arnaud; Degremont, Lionel; Labreuche, Yannick; Daniel, Jean-yves; Dubrunfaut, Thomas; Boudry, Pierre; Haure, Joel; Bedier, Edouard; Ropert, Michel; Herpin, Amaury; Cunningham, Charles; Moal, Jeanne; et al. (International Marine Biotechnology Conference, 2005)
Summer mortality associated with juveniles of the oyster Crassostrea gigas is the result of a complex interaction between the host, pathogens and environment. Divergent selection based on summer survival have been applied to produce families with resistant and susceptible progeny. Here, we describe the use of suppression subtractive hybridization to generate 150 clones that were differentially regulated between resistant and susceptible F2 progeny. The nucleotide sequence of these 150 clones was determined. Among the 25 unique sequences that matched with the products of known genes, those putatively implicated in energy generation (12%) and immune function (16%), systems suspected to be implicated in summer mortality, were extended and analyzed by real time PCR. They were induced in resistant progeny when compared to their susceptible counterparts. An experimental bacterial challenge of oysters, applied with the aim of mimicking one type of summer mortality event, resulted in the significant suppression of most of these transcripts in only progeny that were resistant to summer mortality suggesting the higher capability of resistant oysters to react after bacterial infection. The subtracted clones were also used to produce macroarrays hydridized with probes corresponding to resistant and susceptible oysters sampled during four different in situ and experimental conditionings. Only six clones still appeared differentially expressed between the two types of progeny. Two of them encoded known proteins (Bone Morphogenetic Protein, Precerebellin) putatively implicated in oyster immune pathways. This study has identified potential candidates for further investigation into the functional basis of resistance and susceptibility to summer mortality.